Archaeology, society and identity in modern Japan - Mizoguchi, Kōji, 1963- (Cambridge studies in archaeology., 2006)
This illuminating study examines the role of archaeology in the formation of the modern Japanese nation and the processes by which archaeological practice is shaped by national discourse. Exploring the close interrelationship between archaeology, society and modernity, it helps explain why we do archaeology in the way that we do.